If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8k + 2 = 15k + -12 Reorder the terms: 2 + 8k = 15k + -12 Reorder the terms: 2 + 8k = -12 + 15k Solving 2 + 8k = -12 + 15k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-15k' to each side of the equation. 2 + 8k + -15k = -12 + 15k + -15k Combine like terms: 8k + -15k = -7k 2 + -7k = -12 + 15k + -15k Combine like terms: 15k + -15k = 0 2 + -7k = -12 + 0 2 + -7k = -12 Add '-2' to each side of the equation. 2 + -2 + -7k = -12 + -2 Combine like terms: 2 + -2 = 0 0 + -7k = -12 + -2 -7k = -12 + -2 Combine like terms: -12 + -2 = -14 -7k = -14 Divide each side by '-7'. k = 2 Simplifying k = 2
| -5(7+7x)=245 | | 8k+8=17k-19 | | 10k+11=14k-9 | | 7y=y+48 | | 13=1+6x+6 | | 18*18=24x*6x | | t^2=-10t+11 | | 12*12=16x*4x | | -3(8x-1)=2x-5 | | 6x^2+8x=128 | | 7[1-2x]-3[x-1]= | | 3=2(6)+b | | 221.9352=19.468*w | | x^2+8x+16=-1 | | 6x^4-30x^2+20=0 | | 8(X-2)=72 | | 0=-3x-2y-5 | | 18*18=6x*24x | | 8=92-8x | | 8-e=e | | 6+15y=39 | | (x-1)(x+2)=2(x-4)(x+4) | | 3x+9=3x-8 | | 13+g=31 | | 2p-3r=7 | | 5c=24-c | | t+15=27 | | 64-8x=4x+4 | | 3a+10+5a=-35 | | 4(8-5y)=-2y-4 | | 9x+4=-7 | | 7x+70=14 |